Impact of opioids on oxidative status and related signaling pathways: An integrated view - Zahmatkesh, PhD, Maryam; Kadkhodaee, PharmD, PhD, Mehri; Salarian, MD, PhD student, Ali; Seifi, PhD, Behjat; Adeli, PhD, Soheila (Journal of Opioid Management, 2017)
Background: Opioids produce reactive oxygen species (ROS) which are highly reactive molecules that damage cells and tissues, and are suggested to contribute to the opioid use disorders. Thus, antioxidant supplementation might improve the disturbance in redox (oxidation-reduction) homeostasis. However, randomized trials on antioxidant therapy have not shown beneficial effects. Objectives: The purpose of this review is to shed lights on the oxidative changes resulting from opioid use and to highlight the unanswered questions regarding oxidative profile in an effort to provide a comprehensive view of different aspects of an efficient antioxidant therapy in clinical settings. Methods: The studies were identified and gathered from the PubMed database over the past 16 years (2000-2016). Our search results were limited to articles in English, both animals and human and in vitro and in vivo studies. A total of 50 full text articles were reviewed and summarized. Results: Opioids elevate the level of ROS and decrease the function of enzymatic antioxidants such as superoxide dismutase, catalase, and glutathione peroxidase. They increase the risk of vitamin deficiency and modify gene expression of target cells through ROS production. The effects of opioids on their target cells are exerted through different way and various mechanisms. Conclusion: Opioids modulate the redox homeostasis; therefore, understanding the profile of oxidative changes in individuals with opioid use disorder could be of significant benefits in the clinical setting, to help with selection of an efficient antioxidant therapy and diminishing oxidative damage.